Diagnostic Application of IS900 PCR Using Blood as a Source Sample for the Detection of Mycobacterium avium Subspecies Paratuberculosis in Early and Subclinical Cases of Caprine Paratuberculosis - P. K. Singh; S. V. Singh; H. Kumar; J. S. Sohal; A. V. Singh (Veterinary Medicine International)
Efficacy of IS900 blood PCR was evaluated for the presence of MAP infection. Serum, fecal, and blood samples of kids, young, and adult goats from farm and farmer's herds in Mathura district were also screened by ELISA, microscopy and culture. Of 111 goats (kids: 40, young: 14, adults: 57) screened, 77.5% were positive by blood PCR. Of 76 goats, 90.8% (kids: 87.5% and adults: 94.4%) were positive by PCR. From 21 kids and 14 young goats, 42.8 and 57.1% were positive. gDNA from goats was genotyped as MAP “Indian Bison type”. Of 21 fecal samples of kids examined by microscopy, 66.7% were positive. In ELISA, 9.5 and 57.1% kids were positives as “type I” and “type II” reactors, respectively. Screening 14 young goats by culture of blood clots, 28.6% were positive. Agreement was substantial between PCR and microscopy. It was fair and moderate when PCR and microscopy were compared with type I and type II reactors, respectively. Presence of MAP in non-clinical kids and young goats indicate early or subclinical infection. Blood PCR was rapid, sensitive, and specific assay for detection of MAP in any stage (early, subclinical, and clinical) and age (kids, young, and adult) of goats.